Sport for Development Programmes for Girls and Women: A Global Assessment - Hancock, Meg G; Lyras, Alexis; Jae-Pil Ha (Journal of sport for development, 2013)
A number of researchers along with international sport and humanitarian institutions have advocated the need to leverage the positive impact sport can have on individuals, cultures, and societies. Girls and women, in particular, are underrepresented in social, political, legal, and educational positions in countries around the world. The United Nations (UN) suggests that national and international agencies provide girls and women equal access to sport. Access to sport has the potential to promote physical and mental health, social integration, self-esteem, and skill development. Using a framework of sport for development (SFD) theory and programme objectives set forth by the UN, this study identified trends in sport for SFD programmes for girls and women. Through content analysis, the researchers identified patterns in sports and activities, programme objectives, and intended programme impacts. The number of SFD programmes, objectives, and intended impacts identified in this study suggests that the abundance of policies supporting sport and women’s development is a step forward in the quest for global gender equity and the achievement of various Millennium Development Goals (MDGs). More research is needed to discern under what conditions these programmes assist in the achievement of MDGs and improve the positioning of girls and women in countries around the globe.